Transmission Success of Entomopathogenic Nematodes Used in Pest Control - Labaude, Sophie (Insects, 2018)
Entomopathogenic nematodes from the two genera Steinernema and Heterorhabditis are widely used as biological agents against various insect pests and represent a promising alternative to replace pesticides. Efficacy and biocontrol success can be enhanced through improved understanding of their biology and ecology. Many endogenous and environmental factors influence the survival of nematodes following application, as well as their transmission success to the target species. The aim of this paper is to give an overview of the major topics currently considered to affect transmission success of these biological control agents, including interactions with insects, plants and other members of the soil biota including conspecifics.